Control of growth factor binding and release in bisphosphonate functionalized hydrogels guides rapid differentiation of precursor cells in vitro. (27th November 2015) - Kootala, Sujit; Zhang, Yu; Ghalib, Sara; Tolmachev, Vladimir; Hilborn, Jöns; Ossipov, Dmitri A.
Abstract : Sequestration and active release of BMP-2 in HA-BP hydrogels to precursor cells aid rapid differentiation to osteoblasts. Abstract : An in situ cross-linkable hyaluronan hydrogel functionalized with bisphosphonate (BP) groups allows tunable release of bone morphogenetic protein-2 (BMP-2) determined by the amount of BP groups. The high affinity of matrix-anchored BP groups towards BMP-2 permits guided differentiation of entrapped progenitor cells in 3-D cultures.